2006
DOI: 10.1634/stemcells.2006-0694
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Distribution and Muscle Differentiation of Human Fetal Mesenchymal Stem Cells After Intrauterine Transplantation in Dystrophic mdx Mouse

Abstract: Duchenne muscular dystrophy (DMD) is a common X-linked disease resulting from the absence of dystrophin in muscle. Affected boys suffer from incurable progressive muscle weakness, leading to premature death. Stem cell transplantation may be curative, but is hampered by the need for systemic delivery and immune rejection. To address these barriers to stem cell therapy in DMD, we investigated a fetal-to-fetal transplantation strategy. We investigated intramuscular, intravascular, and intraperitoneal delivery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 75 publications
4
92
2
1
Order By: Relevance
“…Although we successfully found FMCs expressing the mesenchymal marker, vimentin, they were probably too few in proportion (3/ 12 FMCs) to have a significant influence on muscle pathology. Even 0.7% engraftment of fetal MSCs after intrauterine transplantation did not ameliorate disease severity in mdx [17]. Moreover, we did not find FMCs robustly expressing proteins associated with muscle differentiation or integration.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Although we successfully found FMCs expressing the mesenchymal marker, vimentin, they were probably too few in proportion (3/ 12 FMCs) to have a significant influence on muscle pathology. Even 0.7% engraftment of fetal MSCs after intrauterine transplantation did not ameliorate disease severity in mdx [17]. Moreover, we did not find FMCs robustly expressing proteins associated with muscle differentiation or integration.…”
Section: Discussioncontrasting
confidence: 64%
“…The commonest, Duchenne muscular dystrophy, is associated with mutations in the dystrophin gene, which encodes a protein integral to muscle fiber stability [16]. In the main mouse model of Duchenne muscular dystrophy (mdx), transplantation of various stem cell populations has shown therapeutic promise [17][18][19]. Muscle-resident stem cells or satellite cells have been obvious therapeutic candidates for muscular dystrophies [20], as they are activated during normal muscle repair [20,21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We [23] and others [22] have previously reported that fl-MSC possess at least some of the immunomodulatory properties found in adult-derived MSCs. In addition MSCs and, particularly, fetal MSCs are efficiently transduced with integrating vectors and express the corresponding transgene without losing stemness and differentiation capabilities [12,23,33].…”
Section: Moreno Et Almentioning
confidence: 99%
“…Thus, human MSCs from several sources have been shown to reconstitute different tissues after human-sheep [9][10][11], human-mouse [12,13], or human-rat [14] xenogeneic in utero transplantation. Furthermore, proof-of-principle studies have recently stressed the therapeutic potential of human fetal MSCs for the treatment of severe osteogenesis imperfecta both after xenogeneic transplantation into the corresponding mouse model [15], and after allogeneic transplantation in an immunocompetent, HLA-incompatible patient [16].…”
Section: Introductionmentioning
confidence: 99%